ISOLATION OF AN α-GALACTOSIDASE FROM BIFIDOBACTERIUM LONGUM ЛМ-6 AND IDENTIFICATION OF FUNCTIONAL GROUPS OF THE CATALYTIC CENTER OF ENZYME - А. П. Петросьянц (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2016)
Aim. Receiving enzyme of an α-galactosidase of Bifidobacterium longum LM-6. Identification of the functional groups of the catalytic site of the enzyme. Methods. Cultivation and accumulation of biomass of bifidobacteria. Identification of functional groups of the catalytic center of hydrolytic enzyme. Results. On acellular extract of enzyme of an α-galactosidase has been received, based on research and also activity of the studied enzyme is defined. The purification of the enzyme by means of the various organic solvents is carried out. The functional groups of the catalytic center of an α-galactosidase Bifidobacterium longum ЛМ-6 have been identified. It is established that at the active center of an α-galactosidase Bifidobacterium longum ЛМ-6 there are carboxyl and imidazolny groups of proteins, which take part in hydrolysis of galaktooligosakharid. Conclusions. The functional groups of the catalytic site of an α-galactosidase Bifidobacterium longum ЛМ-6 are identified for the first time. It is established that at the active center of an α-galactosidase Bifidobacterium longum ЛМ-6 there are carboxyl and imidazolny groups of proteins.